2022
DOI: 10.1002/ejoc.202200376
|View full text |Cite
|
Sign up to set email alerts
|

Humins‐Like Solid Support for Palladium Immobilization: Highly Efficient and Recyclable Catalyst for Cross‐Coupling Reactions

Abstract: In the present work, a new humins-like resin was prepared using 2,5-bis(hydroxymethyl)furan (DHMF) and maleic anhydride in 2 min at 110 °C. Such a new material was used as a solid support for palladium immobilization. For metal anchoring, encapsulation was the method of choice and palladium was encapsulated by in-situ polymerization. This resulting Pd@DHMF-based catalyst was characterized by solid-state 13 C NMR, FT-IR, SEM, TGA, DSC, XRD, and XPS. To demonstrate proof of concept, Heck and Suzuki cross-couplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 93 publications
0
0
0
Order By: Relevance
“…Watson et al were the first to use Cyrene to replace DMF as the solvent in a Pdcatalysed cross-coupling reaction [72]. Then, other researchers observed that Cyrene could be an excellent alternative medium for the Sonogashira cross-coupling reaction [86,87]. A greener alternative for the synthesis of ureas was proposed, and it was proven that Cyrene could possibly be used industrially as a solvent [88].…”
Section: Cyrene As Replacement Of Dipolar Aprotic Solvents In Reactionsmentioning
confidence: 99%
“…Watson et al were the first to use Cyrene to replace DMF as the solvent in a Pdcatalysed cross-coupling reaction [72]. Then, other researchers observed that Cyrene could be an excellent alternative medium for the Sonogashira cross-coupling reaction [86,87]. A greener alternative for the synthesis of ureas was proposed, and it was proven that Cyrene could possibly be used industrially as a solvent [88].…”
Section: Cyrene As Replacement Of Dipolar Aprotic Solvents In Reactionsmentioning
confidence: 99%